Posted by **sara** on Sunday, February 19, 2012 at 9:31pm.

find lim x->0 3- sqrt x+9/-x

- calculus -
**MathMate**, Sunday, February 19, 2012 at 10:26pm
In general, when there is a sum or difference of square-root terms, multiplying both numerator and denominator by the conjugate is a good strategy.

Lim (3- sqrt( x+9))/(-x )

x->0

= Lim (3-sqrt(x+9))(3+sqrt(x+9))/[(-x)(3+sqrt(x+9)]

x->0

= Lim (9-(x+9))/[(-x)(3+sqrt(x+9)]

x->0

= Lim (-x)/[(-x)(3+sqrt(x+9)]

x->0

= Lim 1/(3+sqrt(x+9)

x->0

=1/6

## Answer this Question

## Related Questions

- math calculus please help! - l = lim as x approaches 0 of x/(the square root of...
- Math- Calculus - I need help with these problems, I cannot find a similar ...
- Math(calculus) - Evaluat d 4lowing1.lim x/|x| x-->0 2.lim x->1 sqrt(x^2+2...
- Calculus - find lim f(x) - lim f(x) x->infinity x->-infinity if f(x)=ln (x...
- CALCULUS - Could someone please solve these four problems with explanations? I'd...
- Calculus - Find the following limits algebraically or explain why they don’t ...
- calculus - A sequence{an} is given by a1=sqrt(2), an+1=sqrt(2*an). a) by ...
- Calculus - show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c...
- Calculus - show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c...
- Check my CALCULUS work, please! :) - Question 1. lim h->0(sqrt 49+h-7)/h = ...